2009
DOI: 10.1016/s1053-8119(09)71945-7
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine DRD2 polymorphism alters reversal learning and associated neural activity

Abstract: In humans, presence of an A1 allele of the DRD2/ANKK1-TaqIa polymorphism is associated with reduced expression of dopamine (DA) D 2 receptors in the striatum. Recently, it was observed that carriers of the A1 allele (A1ϩ subjects) showed impaired learning from negative feedback in a reinforcement learning task. Here, using functional MRI (fMRI), we investigated carriers and noncarriers of the A1 allele while they performed a probabilistic reversal learning task. A1ϩ subjects showed subtle deficits in reversal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 20 publications
10
32
1
Order By: Relevance
“…From this behavioral pattern, the idea evolved that the dACC/RCZ, rather than detecting the occurrence of single negative events, is involved in generating a history of action-outcomes across multiple trials. In agreement with this, we recently observed that the response of the RCZ to negative feedback varied as a function of the number of preceding negative feedback trials (Jocham et al, in press). Behrens and colleagues (2007) showed that activity in the RCZ covaried with subjects’ estimate of the ‘volatility’ of the environment.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…From this behavioral pattern, the idea evolved that the dACC/RCZ, rather than detecting the occurrence of single negative events, is involved in generating a history of action-outcomes across multiple trials. In agreement with this, we recently observed that the response of the RCZ to negative feedback varied as a function of the number of preceding negative feedback trials (Jocham et al, in press). Behrens and colleagues (2007) showed that activity in the RCZ covaried with subjects’ estimate of the ‘volatility’ of the environment.…”
Section: Introductionsupporting
confidence: 78%
“…To analyze the effects of negative feedback due to task rule reversal without a subsequent change in behavior, we contrasted reversal errors with positive feedback (REVERR — ALLPOS). Based on our own previous findings (Jocham et al, in press) and those from Kennerley and colleagues (2006), we furthermore predicted that activity to negative feedback would be higher when this was preceded by another negative feedback trial (NEG+1) than when it was the first negative feedback (NEG+0) after positive feedback trials. The contrast NEG+1 — NEG+0 was calculated and compared between conditions.…”
Section: Methodsmentioning
confidence: 93%
“…The personality trait of extraversion in A1 carriers is associated with altered BOLD responses within the striatum following the delivery of decision outcomes as well as decreased rostral ACC signals following bad outcomes (Klein et al, 2007). This latter activity is likely to relate to the requirements to adjust behavior following bad outcomes, as evidenced by observations that switches from one choice to another by A1 carriers are associated with reduced signal within an orbitofrontal area and ventral striatum, as well as altered signalling within ACC when integrating across preceding negative outcomes (Jocham et al, 2009). By contrast, other polymorphisms of the DRD 2 gene (eg, À141C Ins/Del) are associated with heightened striatal BOLD responses to rewards during performance of a card guessing game (Forbes et al, 2009).…”
Section: Genotypic Variation In Receptor Expression and Decision Makingmentioning
confidence: 97%
“…This DRD2 gene-dose effect has been replicated in a third independent sample in our lab (unpublished data). Others have since reported D2-related genetic influences on behavioral NoGo learning and modulation of striatal activity during negative outcomes (Klein et al, 2007;Jocham et al, 2009). These studies examined the Taq1A polymorphism, which has also been reported to be associated with striatal D2 receptor density (Pohjalainen et al, 1998).…”
Section: Striatal Genetics Of Reinforcement and Decision Makingmentioning
confidence: 99%